Motion sensor-based haptic master controller with finger band soft actuator for surgical robots - Soga, Yuta; Hano, Soichiro; Haraguchi, Daisuke (Advanced robotics, 2024)
This paper presents a motion sensor-based haptic master controller capable of static and dynamic force presentation by the newly invented Finger Band Soft Actuator (FBSA). The master controller operates a surgical assist robot using the $ 6 $ 6 degrees of freedom position and posture data tracked by an optical motion capture. The haptic force presentation can be realized by the pneumatic pressure of FBSA, which can be highly integrated into the controller mechanism to maintain precise manipulability. The FBSA can present a pressing force of 3.7 N for a small-sized finger and 5.1 N for a large-sized finger at an internal pressure of 60 kPa, and there is a monotonically increasing and decreasing relationship between the air pressure and the pressing force. The effectiveness of haptic force presentation by the FBSA was experimentally evaluated in the master-follower operation of a surgical assist robot. Ten subjects performed the task of pulling a suture thread and controlled the manipulation to achieve the directed tension. The experimental result shows that with the four levels of force presentation scheme by the FBSA, the error between suture tension and target operating force is significantly smaller than without force presentation.